Os impactos causados pela insuficiência do manejo de resíduos sólidos entorno de igarapés do nordeste paraense: uma análise da literatura - OLIVEIRA, Rane Larícia Ferreira de (2022)
Bearing in mind that the increase in the world's production of waste promotes environmental degradation, water pollution has been directly affected by the dumping of solid waste (SR) in tributaries that directly affect water health, creating problems for public health. The present work deals with the recurrent environmental impacts caused by insufficient management of RS around streams, with an emphasis on the northeast region of Pará. In order to obtain, through data collection carried out essentially in academic work, the relationship of these environmental impacts. In this work, a bibliographic review research was carried out in order to obtain the necessary data collection for its development. Therefore, it was necessary to carefully read several academic articles and select the impacts caused by the most recurrent RS that affect the health of the environment, subsequently causing problems to public health. The data were presented in table format for further analysis of these impacts. Given this, it was found that a reform is needed in relation to basic sanitation and its RS management in water areas. Where it was possible to conclude that there is a need for awareness about the legal right to basic sanitation and RS management, as well as the proper separation of these wastes to mitigate environmental public health and more aggravating.